Pengaruh Komite Audit dan Human and Social Board Capital Terhadap Sustainability Reporting dengan Kinerja Lingkungan Sebagai Variabel Moderasi di Indonesia Sektor Energi - Andi Irfan; Hijrah Putri (Yayasan Almanar Pujud, 2025)
This research aims to analyze the influence of the audit committee and human and social board capital on sustainability reporting with environmental performance as a moderating variable. This research uses quantitative methods, with a purposive sampling technique and selected 35 energy sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period. Data analysis using Eviews 12, through moderated regression analysis (MRA) was used to process secondary data. The results of this research show that the audit committee and human and social board capital have no effect on sustainability reporting. Environmental performance has a significant influence on sustainability reporting. And the results of the MRA test show that the moderating variable environmental performance cannot strengthen the influence of the audit committee and human and social board capital on sustainability reporting.